Measure to succeed: How to improve employee participation in continuous improvement - Daniel Jurburg; Elisabeth Viles; Martin Tanco; Ricardo Mateo; Álvaro Lleó (Journal of Industrial Engineering and Management (JIEM), 2016)
Purpose: Achieving employee participation in continuous improvement (CI) systems is considered as one of the success factors for the sustainability of those systems. Yet, it is also very difficult to obtain because of the interaction of many critical factors that affect employee participation. Therefore, finding ways of measuring all these critical factors can help practitioners manage the employee participation process accordingly. Design/methodology/approach: Based upon the existing literature, this paper presents a 4-Phase (9 steps) diagnostic tool to measure the main determinants associated with the implementation of CI systems affecting employee participation in improvement activities. Findings: The tool showed its usefulness to detect the main weaknesses and improvement opportunities for improving employee participation in CI through the application in two different cases. Practical implications: This diagnostic tool could be particularly interesting for companies adopting CI and other excellence frameworks, which usually include a pillar related to people development inside the organization, but do not include tools to diagnose the state of this pillar. Originality/value: This diagnostic tool presents a user's perspective approach, ensuring that the weaknesses and improvement opportunities detected during the diagnose come directly from the users of the CI system, which in this case are the employees themselves. Given that the final objective is to identify reasons and problems hindering employee participation, adopting this user's perspective approach seem more relevant than adopting other more traditional approaches, based on gathering information from the CI system itself or from the CI managers.
Keywords: 650; continuous improvement; employee participation; diagnostic tool